ANALISIS RESEPSI PENGALAMAN PENGGUNA NON- PREMIUM MENDENGARKAN IKLAN DENGAN FEAR APPEALS SPOTIFY - Rezky Utami, Nofiyanti; Surayya Ulfa, Nurist; Setyabudi, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Indonesian people are known for their high interest in consuming horror content through various media platforms, including films, true stories, horror literature, and podcasts. According to a 2023 Jakpat survey, interest in horror content among Indonesians stands at 50%. Spotify has leveraged this interest in its communication strategy by employing a fear appeal in advertisements with a unique approach. However, these ads do not consistently translate into purchases and have generated negative feedback on social media. This study investigates how users perceive these horror podcast advertisements. In-depth interviews were conducted with five Spotify users who had listened to horror podcast ads within the past three months. The study aims to identify social, individual, and situational factors influencing the reception offear appeal ads. Findingsreveal a diverse range of userresponses shaped by these factors. Comparative analysis with preferred readings of podcast ads highlights users' reception positions, with many occupying the Negotiated-Oppositional position. This study underscores users' ability to articulate varied responses influenced by social, individual, and situational dynamics, thus illustrating the limited efficacy of Spotify's fear appeal strategy. Recommendations include personalizing ads according to user preferences to enhance effectiveness.